DNA-PKcs phosphorylates hnRNP-A1 to facilitate the RPA-to-POT1 switch and telomere capping after replication. Issue 12 (20th May 2015) - Sui, Jiangdong; Lin, Yu-Fen; Xu, Kangling; Lee, Kyung-Jong; Wang, Dong; Chen, Benjamin P.C.
Abstract: The heterogeneous nuclear ribonucleoprotein A1 (hnRNP-A1) has been implicated in telomere protection and telomerase activation. Recent evidence has further demonstrated that hnRNP-A1 plays a crucial role in maintaining newly replicated telomeric 3′ overhangs and facilitating the switch from replication protein A (RPA) to protection of telomeres 1 (POT1). The role of hnRNP-A1 in telomere protection also involves DNA-dependent protein kinase catalytic subunit (DNA-PKcs), although the detailed regulation mechanism has not been clear. Here we report that hnRNP-A1 is phosphorylated by DNA-PKcs during the G2 and M phases and that DNA-PK-dependent hnRNP-A1 phosphorylation promotes the RPA-to-POT1 switch on telomeric single-stranded 3′ overhangs. Consequently, in cells lacking hnRNP-A1 or DNA-PKcs-dependent hnRNP-A1 phosphorylation, impairment of the RPA-to-POT1 switch results in DNA damage response at telomeres during mitosis as well as induction of fragile telomeres. Taken together, our results indicate that DNA-PKcs-dependent hnRNP-A1 phosphorylation is critical for capping of the newly replicated telomeres and prevention of telomeric aberrations.